2016
DOI: 10.1177/1744806916677761
|View full text |Cite
|
Sign up to set email alerts
|

Selective antagonism of TRPA1 produces limited efficacy in models of inflammatory- and neuropathic-induced mechanical hypersensitivity in rats

Abstract: The transient receptor potential ankyrin 1 (TRPA1) channel has been implicated in pathophysiological processes that include asthma, cough, and inflammatory pain. Agonists of TRPA1 such as mustard oil and its key component allyl isothiocyanate (AITC) cause pain and neurogenic inflammation in humans and rodents, and TRPA1 antagonists have been reported to be effective in rodent models of pain. In our pursuit of TRPA1 antagonists as potential therapeutics, we generated AMG0902, a potent (IC90 of 300 nM against ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 47 publications
1
33
0
Order By: Relevance
“…In contrast, HC‐030031 had no effect on nerve firing following capsaicin stimulation, indicating these effects were not due to non‐specific inhibition of action potential generation (Kerstein et al, ). Similar effects were noted with the chemically distinct AMG0902 (Lehto et al, ). Consistent with this, A‐967079, a potent analogue of AP‐18, also reduced firing of wide‐dynamic range neurons in naïve rats after noxious pinch (McGaraughty et al, ).…”
Section: Trpa1 Channels As Analgesic Targetsmentioning
confidence: 65%
See 3 more Smart Citations
“…In contrast, HC‐030031 had no effect on nerve firing following capsaicin stimulation, indicating these effects were not due to non‐specific inhibition of action potential generation (Kerstein et al, ). Similar effects were noted with the chemically distinct AMG0902 (Lehto et al, ). Consistent with this, A‐967079, a potent analogue of AP‐18, also reduced firing of wide‐dynamic range neurons in naïve rats after noxious pinch (McGaraughty et al, ).…”
Section: Trpa1 Channels As Analgesic Targetsmentioning
confidence: 65%
“…Consistent with this, A‐967079, a potent analogue of AP‐18, also reduced firing of wide‐dynamic range neurons in naïve rats after noxious pinch (McGaraughty et al, ). In addition, TRPA1 KO mice showed attenuated mechanical nociception and reduced firing in response to force in a skin‐nerve preparation (Kerstein et al, ; Lehto et al, ), though the in vivo effect is subtle and varies somewhat among reports (Kwan et al, ; Petrus et al, ). A large data set collected from many studies also supports the role of TRPA1 channels in mechanical hyperalgesia induced by inflammation.…”
Section: Trpa1 Channels As Analgesic Targetsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, these experiments used low potency first-generation TRPA1 inhibitors such as HC030031 and AP18, increasing the likelihood that some of the effects of these compounds could be off-target. Indeed, when high potency TRPA1 inhibitors have been tested in the CFA model (and neuropathic pain models), only limited, if any, efficacy has been observed 35 . It was surprising that TRPA1 KO rats display normal scratching behavior in the calcipotriol-induced chronic itch model, since several high-quality studies showed a robust requirement for TRPA1 in itch using KO mice 12,15,36 .…”
Section: Discussionmentioning
confidence: 99%